2022
DOI: 10.1007/s12325-022-02092-7
|View full text |Cite|
|
Sign up to set email alerts
|

New Versus Old: The Impact of Changing Patterns of Inhaled Corticosteroid Prescribing and Dosing Regimens in Asthma Management

Abstract: Inhaled corticosteroid (ICS)-containing therapies are the mainstay of pharmacological management of asthma. They can be administered alone or in combination with a long-acting bronchodilator, depending on asthma severity, and may also be supplemented with short-acting bronchodilators for as-needed rescue medication. Adherence to asthma therapies is generally poor and characterized by underuse of ICS therapies and over-reliance on short-acting bronchodilators, which leads to poor clinical outcomes. This article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…Exploration of the underlying mechanisms of asthma is the key to develop therapeutic approaches, facilitating research works on asthma phenotype or subtype drugs including severe asthma, resulting in higher efficacy and safety. Good adherence and self-management are important aspects of this process to minimize the influence of asthma in real life, and a previous study showed that the benefits of daily regular administration of ICSs were diminished when adherence was low (50%) ( Singh et al, 2022 ). Therefore, how to improve the adherence of asthma, especially mild-to-moderate asthma, is one of the themes in asthma drug-related research works.…”
Section: Discussionmentioning
confidence: 99%
“…Exploration of the underlying mechanisms of asthma is the key to develop therapeutic approaches, facilitating research works on asthma phenotype or subtype drugs including severe asthma, resulting in higher efficacy and safety. Good adherence and self-management are important aspects of this process to minimize the influence of asthma in real life, and a previous study showed that the benefits of daily regular administration of ICSs were diminished when adherence was low (50%) ( Singh et al, 2022 ). Therefore, how to improve the adherence of asthma, especially mild-to-moderate asthma, is one of the themes in asthma drug-related research works.…”
Section: Discussionmentioning
confidence: 99%
“…A major pathophysiology underlying asthma is airway inflammation [53,54]. Continuous regular use of ICS therapy reduces inflammation, exacerbation risk, and asthma-related mortality across all severities [53][54][55][56][57][58]. The long-term benefit of daily low-dose ICS has even been shown in patients with mild asthma and intermittent symptoms present B 2 days per week [53].…”
Section: Ics Regular Dosing: Benefits and Challengesmentioning
confidence: 99%
“…In a recent review article of efficacy versus systemic activity profiles for various dosing regimens of Bud/Form and FP/Sal, regular daily ICS/LABA dosing regimens (FP dose 250 to 500 µg or equivalent) had higher airway efficacy (in terms of bronchoprotective effects) but similar (and low) systemic activity compared with MART in moderate and moderate-severe asthma [75]. Interestingly, in the current NMA sensitivity analysis that included only low-medium ICS dose arms (FP dose ≤ 500 µg), a numerical trend in favour of FP/Sal over MART in improving AQLQ was seen, which is in line with the results from Singh et al, where regular dosing with medium dose FP/Sal in moderate asthma patients resulted in clinically significant bronchoprotection [75]. It's possible that the exclusion of the high dose ICS arms led to the exclusion of patients with more difficult to control asthma, resulting in the improved HRQoL outcomes overall for FP/Sal.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%